1957
DOI: 10.1037/h0046044
|View full text |Cite
|
Sign up to set email alerts
|

Self concepts in adjusted and maladjusted hospital patients.

Abstract: Difficulties in the development of satisfactory measures of adjustment level characterize part of the criterion problem faced by researchers investigating therapeutic processes. This paper is concerned with one aspect of the utility of the Q technique as a measure of adjustment.The comparison of self and ideal sorts has received much recent attention. Typically, the correlation between S's Q sorts for his concepts of "self" and "ideal self" is used as an index of adjustment level. A low or negative correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1958
1958
1979
1979

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…428]." Although Chase (1957) found lower self-esteem in paranoids, compared to normals, there are other studies which suggest that paranoid schizophrenics tend to show relatively high Real Self-Ideal Self-congruence (Friedman, 1955;Hillson, 1957;Rogers, A., 1958).…”
mentioning
confidence: 99%
“…428]." Although Chase (1957) found lower self-esteem in paranoids, compared to normals, there are other studies which suggest that paranoid schizophrenics tend to show relatively high Real Self-Ideal Self-congruence (Friedman, 1955;Hillson, 1957;Rogers, A., 1958).…”
mentioning
confidence: 99%
“…Self-concept adjustment is an index of the degree to which the person's description is similar to that of adjusted, presumably normal individuals. This method was developed by Chase (1957), who found that maladjusted persons do perceive themselves differently than do adjusted individuals. This measure utilizes the Q-sort technique, comparing a person's self-sort with a normal standard.…”
Section: Methodsmentioning
confidence: 99%
“…The Q sort is very adaptable and has been used as a research technique in the exploration of self concept with various groups. These have included juvenile delinquents (Balester, 1956); hospital patients (Chase, 1957); junior high school boys in group counseling (Caplan, 1957); university student leaders (SnoxelL 19. '53); and students from broken homes (Miller, 1958).…”
Section: Q Techniquementioning
confidence: 99%